2004
DOI: 10.1128/jcm.42.6.2596-2601.2004
|View full text |Cite
|
Sign up to set email alerts
|

Variability of theChlamydia trachomatis omp1Gene Detected in Samples from Men Tested in Male-Only Saunas in Melbourne, Australia

Abstract: C. trachomatis serovars can be differentiated by sequencing the omp1 gene, which codes for the major outer membrane protein (MOMP) (1, 5, 8, 15-17, 25, 31). Preliminary evidence suggests that MOMP is a porin that assembles as ␤ barrels containing conserved domains (CDs) of transmembrane ␤ strands and periplasmic loops and four variable domains (VDs) located on the outer loops (14, 28). Serovars exhibit MOMP sequence heterogeneity that is mainly localized to the VDs (27, 36). Variability in the MOMP sequence is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
14
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 35 publications
4
14
0
1
Order By: Relevance
“…This fact could support the hypothesis proposed by some authors of the existence of an ongoing unrecognised endemic disease among MSM for at least 20 years rather than a new outbreak [45,46]. However, other countries have not confirmed the retrospective detection of undiagnosed cases in stored samples [8,39,47].…”
Section: Epidemiologysupporting
confidence: 63%
“…This fact could support the hypothesis proposed by some authors of the existence of an ongoing unrecognised endemic disease among MSM for at least 20 years rather than a new outbreak [45,46]. However, other countries have not confirmed the retrospective detection of undiagnosed cases in stored samples [8,39,47].…”
Section: Epidemiologysupporting
confidence: 63%
“…A recent study in Melbourne, Australia (8), showed significant differences in serovar distribution between women and men who have sex with men, especially in the relative distribution of the two most common serovars, E (17% and 3%, respectively) and D (7% and 54%, respectively). Serovar G was present in higher proportions of specimens (17% and 26% in women and men who have sex with men, respectively) than in our study (4%).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high prevalence of serovars D/Da and G in this population was different from the overall distribution of C. trachomatis serovars in most populations around the world, in which serovars E, D/Da, and F share the highest prevalence (6). Lister et al (4) extended their study by investigating the distribution of C. trachomatis serovars in 42 women from the same city and found serovars E (40%), F (19%), G (17%), J/Ja (10%), D/Da (7%), and K (7%) (5). This distribution pattern was similar to the worldwide distribution of C. trachomatis serovars except for the relatively low prevalence of serovar D/Da.…”
mentioning
confidence: 99%